2015
DOI: 10.1111/ijd.12761
|View full text |Cite
|
Sign up to set email alerts
|

Multiple microneedling sessions for minimally invasive facial rejuvenation: an objective assessment

Abstract: Skin microneedling is a promising minimally invasive treatment option with the advantage of increased collagen production. However, multiple sessions are usually needed to maintain the improvement achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
100
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 37 publications
10
100
0
8
Order By: Relevance
“…In the subjective evaluation of the respondents, the treatment was evaluated as effective in reducing the signs of aging. Results of our study indicate similar effects of treatments; however, using of needles of 0.5 mm length does not cause bleeding and the patients can immediately return daily routines …”
Section: Discussionsupporting
confidence: 62%
“…In the subjective evaluation of the respondents, the treatment was evaluated as effective in reducing the signs of aging. Results of our study indicate similar effects of treatments; however, using of needles of 0.5 mm length does not cause bleeding and the patients can immediately return daily routines …”
Section: Discussionsupporting
confidence: 62%
“…Osman et al observed that the overall improvement was 70% in fractional (Er: YAG) laser side and 33% in microneedling side. Our study gave better results than their study as degree of improvement in our study was 80% as we used dermapen.…”
Section: Discussionmentioning
confidence: 99%
“…During the period of follow‐up, 3 end points were chosen for evaluation of the volunteers (baseline, after 1 month of treatment [2 sessions] and after 3 months of treatment). Two blinded dermatologists and 2 independent observers were asked to evaluate the improvement of each of the following criteria: atrophic scar appearance, skin texture, and overall satisfaction based on a 5‐point scale (none = 0%, mild = 1%‐25%, moderate = 26%‐50%, good = 51%‐75%, and very good = 76%‐100%) . The results were tabulated and compared to baseline for statistical significance with the Pearson chi‐squared test (Table ).…”
Section: Methodsmentioning
confidence: 99%